1986
DOI: 10.1007/bf00511412
|View full text |Cite
|
Sign up to set email alerts
|

Further studies of the mechanism of counter irritation by turpentine

Abstract: The influence of counter irritation by turpentine (0.2 ml) on zymosan- and carrageenan-oedemas was investigated in the rat. Zymosan-oedema was inhibited by mepyramine and methysergide and by leucopenia. It was not modified by captopril and developed normally in kininogendeficient Brown Norway rats. Leucocytes and mast cell amines but not kinins are thus involved in zymosan-oedema. The last phase of this reaction was inhibited by counter irritation alone, but the odema was largely depressed by counter irritatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…Gamache et al [28] have earlier reported that the carrageenaninduced inflammation is a COX-dependent response and is more effectively controlled with inhibitors of arachidonate COX, but not arachidonate lipo-oxygenase inhibitors. This was supported by the finding of Damas et al [29] that carrageenan induced the release of kinins, polymorphonuclear leukocytes as well as proinflammatory factors (e.g. prostaglandins) that contribute to the development of edema.…”
Section: Discussionsupporting
confidence: 72%
“…Gamache et al [28] have earlier reported that the carrageenaninduced inflammation is a COX-dependent response and is more effectively controlled with inhibitors of arachidonate COX, but not arachidonate lipo-oxygenase inhibitors. This was supported by the finding of Damas et al [29] that carrageenan induced the release of kinins, polymorphonuclear leukocytes as well as proinflammatory factors (e.g. prostaglandins) that contribute to the development of edema.…”
Section: Discussionsupporting
confidence: 72%
“…23,30) The carrageenan-induced edema production is associated with the presence of kinins and polymorphonuclear leucocytes, which involved in the release of pro-in‰ammatory mediators like prostaglandins. 31) The ability of the CEDL to reduce the thickness of the edematous hind paw 32,33) indicates the anti-in‰amma-tory properties of the extract. Thisˆnding seems to justify the traditional use of the plant in the treatment of broiler, ulcers or asthma by the people in Papua New Guinea and India.…”
Section: Discussionmentioning
confidence: 99%
“…The potency of T-kinin to decrease blood pressure was compared to that of standard bradykinin, suggesting the significant ability of T-kininogenase to liberate T-kinin from T-kininogen in vivo (data not shown). These results suggest the hypothesis of Damas et al (1986), who showed that kinin formation could not be induced during inflammation in spite of the elevated level of T-kininogen. Barlas et al (1985) observed an increase in T-kinin in plasma of rats with carrageenin-induced inflammation related to the increase in T-kininogen which does not depend on the activation of a specific Tkininogenase.…”
Section: Resultsmentioning
confidence: 55%